2018
DOI: 10.3390/s18093007
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Rapid Separation and Enrichment of Bone Marrow-Derived Mesenchymal Stem Cells from a Heterogeneous Cell Mixture Using a Dielectrophoresis Device

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) are an important cell resource for stem cell-based therapy, which are generally isolated and enriched by the density-gradient method based on cell size and density after collection of tissue samples. Since this method has limitations with regards to purity and repeatability, development of alternative label-free methods for BMSC separation is desired. In the present study, rapid label-free separation and enrichment of BMSCs from a heterogeneous cell mixture wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…As a result of the differences in the dielectric polarizability of the particles, they show different DEP mobility in the non-uniform electric field, which enables selective separation and isolation with DEP. DEP-based separation has been applied extensively for the separation of many different types of bioparticles, including stem cells [110,[189][190][191], circulating tumor cells (CTCs) [94,192], blood cells [193][194][195], bacteria [96,[196][197][198], viruses [199,200], and DNA [201,202]. For instance, Song et al reported a DEP-based continuous flow microfluidic device to separate human mesenchymal stem cells (hMSC) from their differentiation progenies (osteoblasts) [191].…”
Section: Separation Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the differences in the dielectric polarizability of the particles, they show different DEP mobility in the non-uniform electric field, which enables selective separation and isolation with DEP. DEP-based separation has been applied extensively for the separation of many different types of bioparticles, including stem cells [110,[189][190][191], circulating tumor cells (CTCs) [94,192], blood cells [193][194][195], bacteria [96,[196][197][198], viruses [199,200], and DNA [201,202]. For instance, Song et al reported a DEP-based continuous flow microfluidic device to separate human mesenchymal stem cells (hMSC) from their differentiation progenies (osteoblasts) [191].…”
Section: Separation Of Cellsmentioning
confidence: 99%
“…Due to all these prominent advantages, DEP has become an indispensable particle manipulation technique in microchips developed for biomedical applications [91,101,103]. Consequently, DEP has been applied to control the motion of various bioparticles such as cells, including diseased cells [104][105][106], healthy cells [107][108][109], stem cells [98,110], microorganisms [111][112][113][114][115][116], proteins [117][118][119], DNA [120][121][122], and exosomes [123]. DEP, a prominent particle manipulation technique, has been extensively studied by many research groups and scientists in biosensor and POC applications.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshioka et al separated bone marrow-derived mesenchymal stem cells (BMSCs) from heterogenic cell compound with bone marrow-derived promyelocytes by the DEP method [33]. As the models of BMSCs the human mesenchymal stem cell line (UET-13) were used and human promyelocytic leukaemia cell line (HL-60) as promyelocytes.…”
Section: Microfluidic Cell Sortingmentioning
confidence: 99%
“…Recently, the DEP technique was combined with a bipolar electrode system, and the cells were manipulated in a microfluidic device via electrode arrays in the absence of ohmic contacts (Anand et al, 2015). In addition, a DEP device has been used for cell paring by trapping single cells sequentially (Sen et al, 2013b; Yoshimura et al, 2014; Wu et al, 2017), and a microfluidic DEP device was applied for separation of mesenchymal stem cells (MSCs) from a cell mixture according to their dielectric properties (Yoshioka et al, 2018) and controlled cell differentiation (Yoshioka et al, 2016). Moreover, enrichment and detection of target cancer cells were performed by combining DEP manipulation and impedance measurements (Ngoc-Viet and Jen, 2018).…”
Section: Manipulation Of Cells and Droplets Containing Cellsmentioning
confidence: 99%